The tagasalo personality. [article]. - Udarbe, Margaret Helen
The study investigated Carandang's theory of 'tagasalo" in efforts to describe and explain its origins, development, and dynamics. The possibility of tagasalo being gender-specific and related to birth order, was raised. Ten families were interviewed intensively. In addition, three psychologist tests were administered to the identified tagasalo child and to another child least like the tagasalo. It was found that the tagasalo personality is not systematically related to gender nor birth order, but it can develop out of the need for a child to be different from a sibling who causes emotional upheaval in the family. The tagasalo is responsible and caring person, a listener and a mediator, intent on harmony, and also has a strong need for control and a capacity for emotional distance. Instead of the self-doubting, unloved, compulsive, dependent and passive tagasalo who appears to be acted upon in Carandang's theory, this study found them to be responsible, caring and dependable children who actually take charge in efforts and relieving tension and resolving conflicts in the family. The tagasalo is actually holds power, and who seeks to be in control.